(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The construction industry is a key driver of economic growth. However, operations from the construction industry contribute greatly to environmental damage and unsustainable exploitation of depleted natural resources. The construction industry has thus recognized environmental sustainability as a critical paradigm, primarily due to the necessity to strike a balance between ecological preservation and growing urbanization. The construction industry is essential to the expansion of Abuja, the capital of Nigeria, and it offers chances and problems for sustainable development. The impact of environmental sustainability on Abuja’s construction industry is examined in this study, with particular attention paid to green building techniques, legal frameworks, technological developments, economic ramifications, and societal advantages. This study emphasizes the significance of incorporating environmental factors into urban development strategies to ensure a resilient and prosperous future for Abuja by analyzing the state and possibilities of sustainable construction. The study identified air pollution, Noise pollution and climate change as the high ranked environmental impact of building construction on environmental sustainability while depletion of Natural resources, temperature control and water pollution all ranked low. On factors mitigating environmental sustainability Lack of regulation enforcement, corruption and lack of awareness all ranked high. While, Insecurity, environmental degradation, and political instability all ranked low.